(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
Architecture is a complex form, which is related to the sensory / moral aspects. Therefore, the research problem was concerned with the nature of the architectural event and the inter-people consultation among the following possibilities: 1- Is it the image of the architectural event through time in conflict sometimes and dialogue sometimes. 2 - Or is the image of the architectural event to be dialogue as a thought and use of dialogue as a mechanism? Is the image of the architectural event made up through the conflict as a catalyst and the use of dialogue as a mechanism to achieve it 4 - Or is the conflict a degree of dialogue and dialogue architecture is not the end of the equation, but the result of images resulting from the transition architecture through dialogue? Through the events and events that took place in the architectural arena in the spread of architecture among peoples confirms that it passed through the three points, the research tries to put its hypothesis based on the eternal relationship between conflict and dialogue since the creation of creation, which applies to architecture, so the research assumes that to obtain a spiritual and private building The place can live as long as possible. There must be a relationship between the transfers of the image from the conflict as an intellectual reality to the dialogue as a practical reality that is guided by the architecture to reach its goals. This is done by following the process of image transfer of architectural thought between power and action as conflict is a degree of dialogue to understand the problematic perception of the architectural event to reach the goals of dialogue architecture.